Activation of AMP-Activated Protein Kinase-Sirtuin 1 Pathway Contributes to Salvianolic Acid A-Induced Browning of White Adipose Tissue in High-Fat Diet Fed Male Mice - Lai, Jianfei; Qian, Qianyu; Ding, Qinchao; Zhou, Li; Fu, Ai; Du, Zhongyan; Wang, Cui; Song, Zhenyuan; Li, Songtao; Dou, Xiaobing (Frontiers in Pharmacology, 2021)
Background: Salvianolic acid A (Sal A), a natural polyphenol compound extracted from Radix Salvia miltiorrhiza (Danshen), exhibits exceptional pharmacological activities against cardiovascular diseases. Few studies focus on the anti-obesity property of Sal A, and the underling mechanisms are largely unclear. Recent advances have been made in the understanding of herbal ingredients that contribute to browning of white adipose, which further combats obesity by promoting energy expenditure. Purpose: The present study was designed to investigate the beneficial roles of Sal A on white adipose browning and obesity, and uncover its potential mechanisms. Methods: Both high-fat diet (HFD)-induced obese mice model and fully-differentiated C3H10T1/2 adipocytes induced from mouse embryonic mesenchymal stem cells were employed in this study. Sal A (20 and 40 mg/kg) was administrated by intraperitoneal injection for 13-week. The beneficial roles and mechanisms of Sal A were evaluated by molecular biological detections. Resluts: Sal A treatment significantly attenuated HFD-induced weight gain and lipids accumulation in epididymal fat of mice. Uncoupling protein 1 (UCP1), a precipitating factor and golden marker for white adipocytes browning, was significantly stimulated by Sal A treatment in both white adipocytes tissues and cultured adipocytes. Further mechanistic investigations revealed that Sal A robustly reversed HFD-decreased AMP-activated protein kinase (AMPK) phosphorylation and sirtuin 1 (SIRT1) expression in mice. Genetically silencing either AMPK or SIRT1 using siRNA abolished UCP1 upregulation induced by Sal A. AMPK silencing significantly blocked Sal A-increased SIRT1 expression, otherwise, SIRT1 silencing did not affect Sal A-upregulated phosphorylated-AMPK, indicating AMPK was involved in Sal A-increased SIRT1. Conclusions: Sal A plays an effective modulatory role in the induction of adipocytes browning in HFD-fed mice and cultured adipocytes, and thus may has potential therapeutic implications for the treatment of obesity.